The works of President Edwards ... - Edwards, Jonathan (James R. Tanis collection., 1808)
I. Memoirs of the late Rev. Jonathan Edwards. Farewell sermon. Result of a council at Northampton. Humble inquiry concerning the qualifications for membership in the visible Christian church. Reply to Williams.--II. Work of redemption. Dissertation on the nature of virtue. Observations concerning the mysteries of Scripture.--III. A narrative of many surprising conversions. Thoughts on the revival of religion in New England. An humble attempt to promote explicit agreement in prayer. Life of Rev. D. Brainerd and reflections upon it.--IV. A treatise concerning religious affections. Observations concerning faith. Reasons against Dr. Watts's notion of the preexistence of Christ's human soul.--V. Inquiry into the modern prevailing notions of freedom of will. Miscellaneous observations concerning the divine decrees in general and election in particular. Concerning efficacious grace.